(untitled) (Annals of Medical Research, 2026)
Aim: Tension-type headache (TTH) is the most common primary headache disorder, yet its impact on cognitive and empathic functions remains underexplored. This study investigates the relationship between cognitive domains and empathy in individuals with TTH, considering demographic influences. Materials and Methods: A total of 71 TTH patients (49 females, 22 males) underwent cognitive assessment using the Montreal Cognitive Assessment (MoCA) and Mini-Mental State Examination (MMSE), alongside the Empathy for Pain Scale (EPS) to evaluate cognitive and affective empathy. Statistical analyses included independent samples t-tests and Pearson correlation. Results: No significant differences found were in terms of gender, general cognitive performance (MMSE, MoCA). However, females exhibited significantly higher affective distress, visceral pain empathy, and empathic concern scores. Males showed slower cognitive processing speed on the Trail Making Test. Age negatively correlated with cognitive function but positively with affective distress and empathic concern. Education was positively associated with cognitive scores but not with empathy measures. Executive dysfunction correlated with increased emotional empathy. Conclusion: The findings reveal distinct gender-related differences in empathy among TTH patients, independent of global cognition, and highlight the complex interplay between executive function, age, education, and empathic processing. These insights underscore the need for integrative biopsychosocial approaches in TTH management.